2016
DOI: 10.1002/adem.201500646
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity Enhancement of Binder‐Based Graphene Inks by Photonic Annealing and Subsequent Compression Rolling

Abstract: This paper describes a combination of photonic annealing and compression rolling to improve the conductive properties of printed binder‐based graphene inks. High‐density light pulses result in temperatures up to 500 °C that along with a decrease of resistivity lead to layer expansion. The structural integrity of the printed layers is restored using compression rolling resulting in smooth, dense, and highly conductive graphene films. The layers exhibit a sheet resistance of less than 1.4 Ω □−1 normalized to 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 37 publications
5
43
0
Order By: Relevance
“…Since this type of sintering evolves under nonequilibrium conditions across multiple scales there are not well known, processstructure-property relationships must be developed. Additionally, the adhesion of DW materials on AM surfaces postsintering is also not well understood and warrants further research [24]. As buried metal on dielectric applications, such as through lines and 3D vias in multilayer/multimaterial printing, becomes more relevant, then nonthermal curing methods will also need to be further developed such as electrical sintering to obtain near-bulk σ [25].…”
Section: Challenges Aheadmentioning
confidence: 99%
“…Since this type of sintering evolves under nonequilibrium conditions across multiple scales there are not well known, processstructure-property relationships must be developed. Additionally, the adhesion of DW materials on AM surfaces postsintering is also not well understood and warrants further research [24]. As buried metal on dielectric applications, such as through lines and 3D vias in multilayer/multimaterial printing, becomes more relevant, then nonthermal curing methods will also need to be further developed such as electrical sintering to obtain near-bulk σ [25].…”
Section: Challenges Aheadmentioning
confidence: 99%
“…Graphene ink possesses desirable properties combination, including chemical internees, environmental sustainability, and good electronic conductivity [9][10][11][12][13][14][15][16][17][18]. Compared with other solution-processed conductive inks, such as transparent conductive oxides, the abundance of graphene precursor meets sustained global consumer demands.…”
Section: Introductionmentioning
confidence: 99%
“…Secor and co-workers proposed a graphene ink-nitrocellulose electrochemical sensor for H 2 O 2 determination [33]. Several works have demonstrated that a post treatment of the graphene ink could improve its conductivity through thermal reduction process [12,34,35]. More specifically, Arapov et al [12], Secor et al [34], and Del et al [35] enhanced graphene ink films to sheet resistances of 1.4 Ω/cm, 21.4 Ω/cm, and 30 kΩ/cm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…After solvent exchange the graphene ink was applied to the substrate by screen printing using a 45° angle polyurethane squeegee, at a printing speed of 50 mm/s followed by drying in air at 100 °C for 5 minutes. Subsequently, printed structures were thermally annealed at 350 °C for 30 minutes in air and, finally, compression rolled [1], [14] to reach the target DC sheet resistance of 4 at 10 µm layer thickness. For comparison, W B Q D s a n d C P W s w e r e a l s o s c r e e n p r i n t e d u s i n g a commercial silver ink onto electronic grade PET film (ST506; DuPont Teijin Films; thickness 125 µm).…”
Section: Antenna and Transmission Line Design And Fabricationmentioning
confidence: 99%